Characterization and Antibacterial Activity of Endophytic Bacteria from Flesh Fruit of the Arecaceae Family Against Antibiotic Resistant Bacteria Escherichia coli - Diannita Harahap (Biotropika: Journal of Tropical Biology, 2021)
Bacteria can symbiotic mutualism and synergize with plants in the tissue and do not cause harm to plants. On the other hand, bacteria resistance provides an opportunity to search for antibacterials from natural material without threatening plant biodiversity. The purpose of this study was to characterize and test the antibacterial activity of endophytic bacteria from the fruit of the Arecaceae family against antibiotic-resistant bacteria Escherichia coli. The method used was direct culture on the growth of media in the laboratory by first sterilizing the surface of the flesh of the samples, such as Aren (Arenga pinnata), Coconut (Cocos nucifera), and Sago (Metroxylon sagu). The pure isolates obtained were characterized according to Bergeys Manual for Identification by performing Gram stain, catalase, and coagulase test. The results obtained were five isolates with codes A1, A2, K, S1, and S2 with variation in morphology colonies. Gram staining, catalase, and coagulase verification of the five isolates were groups of Grampositive cocci, catalase-positive, and coagulase-negative bacteria. Based on tests carried out on the characters of the endophytic bacteria, it was obtained a close relationship with the genus Staphylococcus. The results of the inhibitory activity test showed that Staphylococcus sp. K with the highest criteria of 43.26 mm and Staphylococcus sp. A1 with the lowest inhibition criteria with a value of 24.73 mm. Both are categorized as very strong inhibition criteria.